Perencanaan Strategis Untuk Pengembangan Bisnis Fitness Center di Semarang - Angelica Mega Nanda; Sentot Suciarto Athanasius; Thomas Indrajaya (JEMAP, 2019)
Competition in markets creates rivalry between businesses. A company should be able to pass the competitive environment and have competitive advantage with better strategic planning. The fast growing business in Semarang was the body-fitness service business. Consumers select fitness center venues by the company's image, facilities and services. Strategic planning is related to fulfilling the needs of fitness members and customer decisions and becoming success in business. This research objective was to create strategic planning in the field of marketing and operations that focuses primarily on market penetration and developing products to be competitive. The method used was a qualitative and quantitative method of using the IE matrix. The results of the research was corporate strategic planning. In marketing management function, the strategies were to increase number of classes variations in the form of Yoga, TRX and Zumba dance and improve the quality of equipment; and reactivate healthy cafe. In the operational management function, the strategies were perfecting the company's operational program system, improving the quality of equipment and fitness room, provide space, equipment and a new class variation needs, providing the needs of Healthy Café.